A revision of the genus Lamellipalpus Maulik, 1921 (Coleoptera, Lampyridae) - Brancucci, Michel; Geiser, Michael (Zootaxa, 2009)
The genus Lamellipalpus Maulik, 1921 is revised. In total, 12 species are recognized 7 of which (with 1 additional new subspecies) are described as new to science: L. atripalpis sp. nov. (India, Meghalaya), L. flavomarginatus sp.nov. (India, Mizoram), L. kubani sp. nov. (W Thailand), L. longipalpis sp. nov. (Nepal), L. nepalensis sp. nov. (Nepal), L. pacholatkoi sp. nov. (NE India), L. p. turaensis ssp. nov. (India, Meghalaya, Tura Hills) and L. sinuaticollis sp. nov. (India, Meghalaya). L. sallei Pic, 1924, syn. nov. is newly synonymized with L. bombayensis Maulik, 1921. All the species are illustrated and a key for their identification is given. Eugeusis lineatus Pic, 1921 is transferred to Lamellipalpodes Maulik, 1921.